Accounting for decision making and control - Zimmerman, Jerold L. , 1947- (McGraw-Hill/Irwin, 2011)
Provides students and managers with an understanding appreciation of the strengths and limitations of an organization's accounting system. This book demonstrates that managerial accounting is an integral part of the firm's organizational architecture, not just an isolated set of computational topics